Analysis of Student Problem Solving Skill and Activity Concentration on a Senior High School - Hendriana, Heris; Purwasih, Ratni; Triawan, Erwin; Prasetio, Yudi; Satria, Tri (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
The aim of the research to know the level of student problem solving skill of Senior high school students on their mathematical problem and activity concentration. The object of the research was conducted at one of Senior high school of Cimahi. the Subject of the research is all twelve grades of Senior high School Students of Science Program in Cimahi. The research used descriptive qualitative research to describe the student analysis error on doing the question of problem solving ability. The data of the research was found using diagnostic of series and rows and also student questionnaire. Data collecting technique used Miles and Huberman concept that are reduction data, reporting data and draw the conclusion. The result of the research are: (1) the level of the ability to solve the problem is still low (2) the common student error did not understand the questions and have no ability to communicate in mathematical form. (3) the student’s activity is rated strong. Some solutions can be given to increase student problem solving ability through practice or question drill structured and gived the variety questions as material practice.